2019
DOI: 10.21037/tlcr.2019.10.23
|View full text |Cite
|
Sign up to set email alerts
|

The role of the gut microbiome on the efficacy of immune checkpoint inhibitors in Japanese responder patients with advanced non-small cell lung cancer

Abstract: Background: Cancer immunotherapy is being developed as a promising alternative for advanced nonsmall cell lung cancer (NSCLC). However, novel biomarkers are required to select patients that will benefit from treatment with immune checkpoint inhibitors (ICIs) for a long period of time. The gut microbiome is expected to be a promising biomarker of ICI response owing to the regulation of the immune status within the host.Methods: In this retrospective study, we included 17 Japanese patients with advanced NSCLC wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 18 publications
3
58
1
Order By: Relevance
“…Although there are studies correlating phylum Bacteroidetes with poor response from ICIs [12,17], we also observed several other studies were suggestive of a positive impact [6,13,18]. In fact, an earlier preclinical study demonstrated a cause and effect role of certain Bacteroidetes (e.g.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Although there are studies correlating phylum Bacteroidetes with poor response from ICIs [12,17], we also observed several other studies were suggestive of a positive impact [6,13,18]. In fact, an earlier preclinical study demonstrated a cause and effect role of certain Bacteroidetes (e.g.…”
Section: Discussionsupporting
confidence: 48%
“…The vast majority are prospective studies. Among them, 10 studies [6,9,[12][13][14][15][16][17][18][19] had response/e cacy data and 3 studies [17,20,21] had AEs data using ICI therapy, and 1 study had both [17]. Of note, the documented AEs in that 3 studies [17,20,21] were virtually all irAEs.…”
Section: Common Features In Gut Microbiome Correlate With the Treatmementioning
confidence: 99%
“…In addition, patients who were not responsive to ICI had more Staphylococcus present in their gut, a bacterium that is often elevated in cancer patients (9,36). In another study, patients with abundant Lactobacillus and Clostridium in their stool tended to have a longer benefit from ICI than those with a lower abundance (49). When assessing microbiota composition in the stool samples of patients with advanced NSCLC treated with nivolumab, subjects with high microbiome diversity had significantly longer progression-free survival compared to those with low diversity (50).…”
Section: Effects Of the Microbiome On Cancer Therapymentioning
confidence: 99%
“…38,48 Furthermore, the relative abundance of members of the Ruminococcaceae family 48 correlated with the density of PD-1 + CD8 + T cells among (TILs). Again, another report analyzing the gut microbiota composition from 17 NSCLC patients revealed that Lactobacillus, Clostridium, and Syntrophococcus were overrepresented in R, while Bilophila or Sutterella 49 was dominant in NR. Of note, the presence of Bilophila drastically shortened the time to treatment failure.…”
Section: Gut Oncomicrobiota Signatures Associated With Response To Icismentioning
confidence: 99%
“…Of note, the presence of Bilophila drastically shortened the time to treatment failure. 49 A Chinese prospective study including 63 NSCLC cancer patients revealed Parabacteroides and Methanobacteriaceae as species and family members associated with PFS >6 months while stool enriched in Veillonella, Selenomonadales, and Negativicutes 50 predicted shorter PFS during PD-1 blockade. In sharp contrast with these findings, ileal enrichment with Veillonella, Selenomonadales, and Negativicutes was found to be associated with increased TIL and favorable prognosis during oxaliplatin-based chemotherapy in proximal colon cancer patients.…”
Section: Gut Oncomicrobiota Signatures Associated With Response To Icismentioning
confidence: 99%